EFFECT OF GENDER DIVERSITY ON CORPORATE BOARDS ON THE FINANCIAL PERFORMANCE OF SAUDI COMPANIES: A SURVEY STUDY (Lex localis - Journal of Local Self-Government, 2025)
This study investigates the associations between gender diversity (GD) within the board of directors (BD) and financial performance (FP) in Saudi Arabia. It aims to provide empirical evidence on how the inclusion of women in top corporate governance structures impacts firms’ economic outcomes in the context of a conservative and emerging market. By focusing on the Saudi corporate landscape, where recent reforms under Vision 2030 have encouraged female participation in leadership roles, this research addresses a timely and socially relevant issue.Specifically, the study examines whether the representation of women on the board of directors influences key financial indicators, including Return on Assets (ROA), Return on Equity (ROE), and Tobin's Q ratio. These indicators were chosen to capture both accounting-based and market-based measures of performance, providing a comprehensive view of financial outcomes. The presence of gender diversity is hypothesized to enhance board deliberations and decision-making quality, which could, in turn, improve financial results.To test this hypothesis, the static panel data approach is employed, using a dataset that includes 78 publicly listed Saudi companies across various sectors over the period 2018–2024. This method allows for controlling firm-specific effects and provides robust estimates of the relationship between GD and FP. The period selected encompasses years of notable regulatory and social change in the Kingdom, making it particularly suitable for evaluating the effects of gender reforms on corporate governance.The findings of the study reveal that gender diversity on boards has a positive and statistically significant effect on financial performance when measured by ROA and ROE. These results suggest that companies with more gender-diverse boards tend to utilize their assets more efficiently and generate higher equity returns. However, when financial performance is measured using Tobin’s Q ratio; a market-based indicator reflecting investor expectations the relationship with gender diversity is found to be statistically insignificant. This divergence may imply that while internal efficiency improves with gender-diverse governance, external perceptions by investors are slower to reflect these improvements or are influenced by additional market variables.These discoveries contribute to the growing body of literature that explores the intersection of board composition and firm performance. In the specific context of Saudi Arabia, they offer valuable insights for shareholders, regulators, and policymakers striving to enhance corporate governance and promote gender inclusivity. The study underscores the importance of fostering diversity at the top levels of organizational leadership, not only as a matter of equity but also as a strategic asset that can improve firm performance. Future research could further investigate the moderating effects of industry type, firm size, or the proportion of independent directors on the GD–FP relationship.